Urban Sufism: The New Spirituality of Urban Communities in Indonesia - Mustofa, Farid (Jurnal Filsafat "WISDOM", 2012)
The backgrounds of this research was the three major difficulties experienced by Indonesia nation after the political transformation of 1998, i.e. economic crisis in 1998, terrorism, and natural disasters. People who live in difficult situations need a way to solve the problem. Besides the physical solution, mental solutions (e.g. spirituality and religiosity) have significant role as a way out of trouble. In this context, the excitement of spiritualism in the community, whether urban or rural, is marked the strengthening of local spirituality and beliefs, for example sufism. Sufism has become a necessity of life of modern society. Even recently there is an interesting phenomenon of the urban community stretching to the study of Sufism. This study focused on understanding and history of Sufism in general, the emergence ofÂ  Urban Sufism in Indonesia, the types and the contributing factors.This research is a library research which used philosophical hermeneutic method. Elements of methods used are description, historical, language analytics, verstehen, and heuristics.The result of the research are described as follows: Urban Sufism is a religious social phenomenon of urban society arising from the quest on spiritual dimension of religion. One significant factor that encourages the emergence of this movement isÂ  people missed the spiritual aspect wich is almost missing in daily life. Based on the organization or community, urban Sufism has different shapes, such as Salat Khusyuk Community and "Majelis Zikir".Keywords: sufism, urban society, spiritual dimension